Comprehensive Determination of Mycobacterium tuberculosis and Nontuberculous Mycobacteria From Targeted Capture Sequencing - He, Ya; Gong, Ziying; Zhao, Xiaokai; Zhang, Daoyun; Zhang, Zhongshun (Frontiers in Cellular and Infection Microbiology, 2020)
Infection of mycobacterium tuberculosis (MTB) and nontuberculous mycobacteria (NTM) challenge effective pulmonary infectious diseases control. Current phenotypic and molecular assays could not comprehensive and accuracy diagnose of MTB, NTM and drug resistance. Next generation sequencing allows an “all-in-one” approach providing results on expected drug susceptibility testing (DST) and the genotype of NTM strains. In this study, targeted capture sequencing was used to analysis the genetic backgrounds of 4 MTB strains and 32 NTM pathogenic strains in 30 clinical samples, including 14 sputum specimens and 16 bronchoalveolar lavage fluid samples. Through comparing with other TB diagnostic tests, we proved targeted capture sequencing could be used as a highly sensitive (91.3%) and accurate (83.3%) method to diagnosis TB, as well as MGIT 960. Also, we identified 7 NTM strains in 11 patients, among them, 7 patients were MTB/NTM co-affected, which indicated it was a meaningful tool for the diagnosis and treatment of NTM infection diseases in clinic. However, based on a drug-resistant mutation library (1325 drug resistance loci), only 9 drug resistance strains and 22 drug resistance loci were discovered, having considerable discordance with the drug-resistant results of MGIT 960. Our finding indicated that targeted capture sequencing approach was applicable to comprehensive and accurate diagnose MTB and NTM. However, from data presented here, the DST results identified by NGS showed a relative low consistency with MGIT 960, especially in sputum samples. Further work would be done to explore the reasons for low drug-resistance detection rate of NGS.